Acute Ischaemic Stroke in Patients Treated with Direct Oral Anticoagulants: Potential Causes, Clinical Characteristics, and Short-Term Outcomes - Katarzyna Sawczyńska; Ewa Włodarczyk; Aleksandra Pawlicka; Bartosz Kołodziejczyk; Paweł Wrona; Kamil Wężyk; Tomasz Homa; Paulina Sarba; Dominik Wróbel; Kaja Zdrojewska; Maria Sobolewska; Dawid Rolkiewicz; et al. (Stroke Research and Treatment)
Introduction. Direct oral anticoagulants (DOAC) are the first-line treatment for primary and secondary acute ischaemic stroke (AIS) prevention in patients with nonvalvular atrial fibrillation (NVAF), but a significant percentage of patients develop AIS despite being treated with DOAC. As the number of DOAC-treated patients is growing, so is the number of patients with AIS on DOAC. The aim of the study was to assess the incidence of AIS with prestroke DOAC treatment among patients hospitalised in the University Hospital in Kraków, to analyse the clinical characteristics of AIS occurring in patients on DOAC, and to identify potential causes of treatment ineffectiveness in this group. Materials and Methods. In the study, we included all patients hospitalised in the Department of Neurology of the University Hospital in Kraków within one year (July 2022 to June 2023) with the diagnosis of AIS. The group was divided into two subgroups of patients with and without prestroke DOAC treatment. Based on medical files, we retrospectively analysed the profile of cardiovascular risk factors, stroke severity (assessed with National Institutes of Health Stroke Scale, NIHSS), use of causative stroke treatment and short-term outcomes (defined as NIHSS score, modified Rankin scale (mRS) score at discharge, in-hospital mortality, and secondary intracerebral haemorrhage among patients treated with mechanical thrombectomy, MT). Within the DOAC-treated subgroup, we looked for potential causes of AIS occurring despite DOAC treatment (valvular AF, poor adherence to treatment, underdosing, other prothrombotic conditions, aetiology of stroke other than thromboembolic, and drug-drug interactions). Results. In the study, we included 768 AIS patients. 109 (14.2%) had a history of prestroke DOAC treatment. A potential cause of DOAC treatment failure was identified in the majority of them (n=63, 57.8%). Patients with prestroke DOAC treatment had worse functional condition before stroke and higher stroke severity on admission but similar short-term outcomes and similar short-term effects of treatment with MT. DOAC (+) and DOAC (-) patients had different profiles of cardiovascular risk factors and different factors associated with short-term outcome. Conclusions and Clinical Implications. A potential cause of AIS occurring in DOAC-treated patients can be identified in most cases and in many of them prevented.